A density functional theory insight towards the rational design of ionic liquids for SO2 capture1. Issue 20 (28th May 2015) - García, Gregorio; Atilhan, Mert; Aparicio, Santiago
<x xml:space="preserve">Abstract</x> A systematic density functional theory (DFT) analysis has been carried out to obtain information at the molecular level on those factors related to efficient SO2 capture by ionic liquids. A set of 55 ionic liquids, for which high gas solubility is expected, has been selected.